Firms' expectations and price-setting: Evidence from micro data - Lena Boneva; James Cloyne; Martin Weale; Tomasz Wieladek (Bank of England, External Monetary Policy Committee Unit, 2016)
In many forward-looking macroeconomic models, such as the New Keynesian model, firms' expectations about the future play a key role in determining outcomes today. We examine this hypothesis using a novel panel dataset on firms actual and expected price changes collected by the Confederation of British Industry. Our microeconometric approach overcomes the identification issues faced by previous empirical studies. The results suggest that firms' expectations play a key role in their price-setting behaviour, with a coefficient on firm's expectations consistent with the discount factor typically assumed in macroeconomic models.
Keywords: C23; C26; E31; 330; Pricing-setting; survey data; inflation expectations; New Keynesian Phillips Curve